Síndrome del cuidador en familiares de pacientes con enfermedades crónico-degenerativas atendidos por la unidad de medicina familiar del Hospital Manuel Ygnacio Monteros Valdivieso IESS-Loja. Periodo abril- septiembre 2013. - Vásquez Jaramillo, Luis Eduardo (2014)
The present study focuses on knowing the Caregiver Overload Syndrome, a disorder currently forgotten and ignored by the health care system; it occurs in people who play the role of primary caregiver of a dependent person, it is characterized by the physical and mental exhaustion of the person who has suddenly face a new situation for which is not ready and it consumes all his time and energy. The study was conducted on families caregivers responsible for the care of patients with chronic - degenerative diseases from Hospital Manuel Ygnacio Monteros Valdivieso IESS - LOJA, it is also to know the main alert symptoms associated with the syndrome of caregiver overload; to establish the primary caregiver personality traits; identify the socio-demographic profile of the caregiver in our society and design an intervention plan in prevention of the Mental health of the carer. The study could show that people who are patients with chronic - degenerative diseases present caretaker overload syndrome, the main psychological symptoms associated with the syndrome are: anxiety and depression; the gender that prevails in the caregiver syndrome is the women between 61 to 70 years, marital status married, wife of the patient, with complete secondary education, and whose personality traits are Anancasticos. KEY words: Overload syndrome of Informal caregiver, caregiver, chronic degenerative diseases, Formal caregiver.